PENGARUH MOTIVASI KERJA, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA ABON BESUKI JAYA 99 - Kenny Clara Kusumaningrum; Wagiyem (JURNAL ILMIAH EDUNOMIKA, 2025)
This research focuses on identifying and analysing the role played by work motivation, employee competence, and work discipline to predict or influence employee performance at Abon Beski Jaya 99 Boyolali. This study’s population is 55 Abon Besuki Jaya 99 Boyolali employees. To obtain precise and representative data in this study, the saturated sampling method with the participation of 55 employees was used as research samples. Data were collected via questionnaires, and multiple regression analysis was used to analyze the data. When analysed individually, this research found that work motivation, skills, and discipline exhibit a positive and statistically significant correlation with employee performance. A simultaneous analysis of these variables also confirms their significant impact on employee performance. Keywords: Competence, Employee Performance, Work Motivation, Work Ethic